VD_FINDINFO HC / 2011 / 627 vom 27. September 2011 - VD Tribunal cantonal (2011)
AVANCE DE FRAIS, SUSPENSION DE LA PROCÉDURE | 126 al. 1 CPC (CH), 98 CPC (CH), 10 TFJC (2010), 18 al. 1 TFJC (2010), 9 al. 1 TFJC (2010)